Policy Goals of Contract Arrangements in Primary Care in Jeopardy: A Cross-Sectional Consumer Satisfaction Survey of Community Residents in Hangzhou, China - Ren, Lixian; Ren, Jianping; Liu, Chaojie; He, Mengyan; Qiu, Xiantao (Frontiers in Public Health, 2022)
Objective China is attempting to establish a voluntary contracting system in primary care. This study aimed to determine the degree of consumer satisfaction with the entitlements of contract arrangements and its associated factors. Methods A stratified cluster sampling strategy was adopted to recruit study participants from three administrative districts of Hangzhou municipality, each containing six residential communities. In each community, 50 households were recruited. A questionnaire was administered through face-to-face interviews with members of the households who signed a contract with community health centers, to collect data regarding their sociodemographic characteristics, health conditions, and knowledge of and attitudes toward the contract entitlements. Consumer satisfaction was measured using six items rated on a five-point Likert scale ranging from “1=very dissatisfied” to “5=very satisfied” and a summed score was calculated. A mixed linear regression model was established to identify individual predictors of consumer satisfaction after adjustment of the random (intercept) effect of household clusters. Results Overall, the respondents reported low levels of awareness and understanding of the contract entitlements, with an average knowledge score of 8.21 (SD = 3.74) out of a maximum possible of 19. The respondents had relatively lower levels of satisfaction (satisfied or very satisfied) with their prioritized entitlements (51.5%) and hospitals at home and telemedicine services (31.3%), compared with the contract and insurance policies (85.5%) and medical services provided (87.0%). Female gender, older age, chronic conditions, and perceived better health were associated with higher levels of satisfaction, while poor awareness and knowledge were associated with lower levels of satisfaction. Conclusion The study participants perceived limited benefits from the contract arrangements in primary care, which may jeopardize the policy purpose of the arrangements to encourage patients to use primary care as the first contact point in accessing health care services. It is evident that consumer satisfaction with the contract entitlements varies by healthcare needs. Lower levels of satisfaction are associated with poor awareness and knowledge of the entitlements.